TCF4, Schizophrenia, and Pitt-Hopkins Syndrome - Blake, Derek J. (Oxford University Press, 2010)
Genome-wide association studies allied with the identification of rare copy number variants have provided important insights into the genetic risk factors for schizophrenia. Recently, a meta-analysis of several genome-wide association studies found, in addition to several other markers, a single nucleotide polymorphism in intron 4 of the TCF4 gene that was associated with schizophrenia. TCF4 encodes a basic helix-loop-helix transcription factor that interacts with other transcription factors to activate or repress gene expression. TCF4 mutations also cause Pitt-Hopkins Syndrome, an autosomal-dominant neurodevelopmental disorder associated with severe mental retardation. Variants in the TCF4 gene may therefore be associated with a range of neuropsychiatric phenotypes, including schizophrenia. Recessive forms of Pitt-Hopkins syndrome are caused by mutations in NRXN1 and CNTNAP2. Interestingly, NRXN1 deletions have been reported in schizophrenia, whereas CNTNAP2 variants are associated with several neuropsychiatric phenotypes. These data suggest that TCF4, NRXN1, and CNTNAP2 may participate in a biological pathway that is altered in patients with schizophrenia and other neuropsychiatric disorders.